Pengaruh pH dan Konsentrasi Larutan Terhadap Penyerapan Zat Warna Rhodamin B Menggunakan Biosorben Kulit Pisang Kepok (Musa Balbisiana Colla) - Rahmatika, Aljumaatul; Nasra, Edi; Dewata, Indang; Sanjaya, Hary (Periodic, 2019)
Abstract ─ Pollution that occurs in the community is caused by solid or liquid waste. One of the pollutants that are discharged into the environment are dyes. The dye waste originates from the coloring and dyeing process which is discharged directly in large quantities into the environment without prior processing. While the environment has certain limits to degrade the incoming compounds or dyes. One alternative method used to remove Rhodamin B dyes is the biosorption method. This method is believed to be able to eliminate pollutants in the waters because of its absorption which is quite effective at a relatively low cost, easy workmanship and the materials used are easily obtained such as kepok banana peels. This research uses the Batch method by looking at the effect of pH and concentration of the solution on the absorption of Rhodamin B by kepok bananas (Musa balbisiana Colla). The results showed that the optimum conditions occurred at pH 3 with 58% absorption of Rhodamin-B, concentration of 120 mg / L with 96% absorption of Rhodamin-B. The interaction between adsorbent and adsorbate is determined by the study of adsorption isotherms including the Langmuir isotherm and the Freundlich isotherm. In order to obtain Langmuir equilibrium with qmax of 25.9067 mg/g. Characterization of kepok banana peel using FTIR to see functional groups after activation.Keywords : Biosorption, Rhodamin-B, kepok banana peel (Musa balbisiana Colla), Batch method